Atividades remotas no ensino de Ciências da Natureza conforme a Base Nacional Comum Curricular em tempos de pandemia - SANTANA, Nayara Layane das Mercês (2023)
The National Common Curricular Base (BNCC) was a requirement of international organizations, the Federal Constitution of 1988, the Law of Guidelines and Bases of National Education (BRASIL, 2012) of 1996 and three of the goals of the National Education Plan (PNE) 2014-2024. Brazil, like other countries in the world, faces a complex situation caused by the Covid-19 pandemic, a disease caused by the new coronavirus, SARS-CoV-2, whose clinical picture varies from asymptomatic infections to severe respiratory crisis (BRASIL, 2020). With the social isolation measure adopted as a means of controlling and containing the spread of Covid-19, as well as a means of avoiding a possible collapse of Brazilian public health, schools began to suspend their face-to-face activities as of March 2020. This article aimed to verify whether natural science teachers were able to program their remote activities as established by the BNCC. The search for papers took place in the “Google Scholar” database from August to September, with the search being initially carried out by titles, reading of abstracts, and in some cases reading the entire document, based on the search for keywords. The work was developed with teachers in the area of Natural Sciences working in Elementary and Middle School, one being a private school teacher in the city of Castanhal-PA and the other public schools in the city of Curuçá-PA. The sample consisted of fifteen (15) teachers, aged between 24 and 50 years. The questionnaire consisted of 13 questions related to the theme. Of the 13 questions, 09 were objective and 04 were discursive questions, with an application date between the 14th and 24th of September 2021. The disclosure took place through invitations sent by the instant messaging application (WhatsApp) to the teachers. In 2019, a survey was carried out on the Technological Profile of Elementary Students at the State Elementary School Jupiter Maia de Curuçá - PA, the work had the collaboration of 42 9th grade students, aged 11 to 15 years, the The objective of the research was to analyze the use of digital technologies to evaluate their use in learning. The information obtained in the surveys were organized and analyzed using figures constructed using Google Forms and Excel. The results of the survey carried out in 2019 before the pandemic pointed out that most students have wide access to technological devices, however they need Digital Literacy. Faced with the new form of teaching that emerged in the Brazilian scenario, it was possible to verify that the BNCC is helping in the planning of remote classes, but that it is not fully worked on as it should with its skills and competences.